Interactions between capture fisheries and aquaculture: the case of the eel (Anguilla anguilla L., 1758). - CICCOTTI, ELEONORA (FAO, 2005)
The European eel, Anguilla anguilla L., is recognised today as an international marine species and a shared resource among European and Mediterranean countries. For this species, major problems exist in relation to a continent-wide decline in recruitment observed in the course of the last decades, and to a contraction in adult eel capture fisheries. In relation to this situation, debate on the possible measures to protect the European eel stock is topical at the present moment, also in relation to a series of steps undertaken by the European Community.